2012
DOI: 10.1097/spv.0b013e3182724648
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative and Postoperative Gastrointestinal Complications Associated With Laparoscopic Sacrocolpopexy

Abstract: The rates of GI complications in laparoscopic sacrocolpopexy are low. Prior abdominal surgery was associated with an increased risk of functional GI complications, but not bowel injury. This information should assist surgeons with preoperative patient counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
1
4
1
1
Order By: Relevance
“…We found patient's age and prior laparotomy were significantly associated with the occurrence of significant GI morbidity, which is consistent with the results of previous studies [6,7]. The association of age and postoperative ileus has been also found in other abdominal surgeries [16,17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found patient's age and prior laparotomy were significantly associated with the occurrence of significant GI morbidity, which is consistent with the results of previous studies [6,7]. The association of age and postoperative ileus has been also found in other abdominal surgeries [16,17].…”
Section: Discussionsupporting
confidence: 92%
“…And it has been found that patients undergoing laparoscopic colon resection have lower levels of systemic cytokines after surgery compared with those who had open procedures [22]. Although it is unknown that the same benefit of laparoscopic approach can be applied to SCP, a recent paper evaluating GI complications after laparoscopic SCP showed low rates of postoperative ileus or small bowel obstruction [7]. A prospective, randomized trial evaluating whether laparoscopic SCP may reduce the risk of significant GI morbidity compared with laparotomic SCP is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate is similar to that reported in other studies in which the mesh is covered by peritoneum. 17 Our study provides further evidence that omitting reperitonealization of the mesh is safe.…”
Section: Discussionmentioning
confidence: 75%
“…Актуальность. Моторно-эвакуаторная дисфункция желудочно-кишечного тракта широко распространена в послеоперационном периоде и возникает не только после больших операций на брюшной полости, забрюшинном пространстве, но и после небольших по объему оперативных вмешательств, в том числе выполненных лапароскопически [1,2]. Целью…”
Section: влияние L-аргинина на скорость разрешения послеоперационногоunclassified